Language, food and gentrification: signs of socioeconomic mobility in two Gothenburg neighbourhoods - Järlehed, Johan; Nielsen, Helle Lykke; Rosendal, Tove (Multilingual Margins: A journal of multilingualism from the periphery, 2018)
This paper examines at how language and food intersect and interact in gentrification processes. As a capital-driven social process aiming at enhancing the socioeconomic value of urban space, gentrification implies mobility both in the sense that it attracts new people, businesses and capital to an area, and in the form of displacement of less affluent and prestigious people, businesses and semiotic resources from central to marginal urban spaces. The paper examines linguistic and visual traces of such mobilities in two neighbourhoods in Gothenburg, Sweden. Based on the observation that food and food practices are central for the production and reproduction of social distinction, the analysis centres on food related establishments and signs. In particular, it discusses the distinction-making function of prestigious languages, elite gastronomic registers, and gourmet food trucks, and how these depend on the marginalization of low status languages, popular gastronomic registers and cheap generic food carts. People’s interaction with these resources contributes to the reconfiguration of social and urban space.